Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acs.jmedchem.9b00348
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of 3-Oxabicyclo[4.1.0]heptane, a Non-nitrogen Containing Morpholine Isostere, and Its Application in Novel Inhibitors of the PI3K-AKT-mTOR Pathway

Abstract: 4-(Pyrimidin-4-yl)­morpholines are privileged pharmacophores for PI3K and PIKKs inhibition by virtue of the morpholine oxygen, both forming the key hydrogen bonding interaction and conveying selectivity over the broader kinome. Key to the morpholine utility as a kinase hinge binder is its ability to adopt a coplanar conformation with an adjacent aromatic core favored by the morpholine nitrogen nonbonding pair of electrons interacting with the electron deficient pyrimidine π-system. Few selective morpholine rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The phosphoinositide-3-kinase (PI3K)-AKT-mammalian target of rapamycin (mTOR) pathway is involved in a number of cellular processes such as proliferation, metabolism, autophagy, differentiation, and survival . Therefore, Hobbs et al synthesized compound 12 , characterized by the presence of a 3-oxabicyclo[4.1.0]­heptane all-carbon quaternary morpholine surrogate, as a multitarget (PI3K/AKT/MTOR) inhibitor . The X-ray structure of 12 revealed coplanarity between the pyrimidine ring and the 3-oxabicyclo[4.1.0]­heptane moiety.…”
Section: Matched Molecular Pairs Of Quaternary Versus Secondary/terti...mentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphoinositide-3-kinase (PI3K)-AKT-mammalian target of rapamycin (mTOR) pathway is involved in a number of cellular processes such as proliferation, metabolism, autophagy, differentiation, and survival . Therefore, Hobbs et al synthesized compound 12 , characterized by the presence of a 3-oxabicyclo[4.1.0]­heptane all-carbon quaternary morpholine surrogate, as a multitarget (PI3K/AKT/MTOR) inhibitor . The X-ray structure of 12 revealed coplanarity between the pyrimidine ring and the 3-oxabicyclo[4.1.0]­heptane moiety.…”
Section: Matched Molecular Pairs Of Quaternary Versus Secondary/terti...mentioning
confidence: 99%
“…54 Therefore, Hobbs et al synthesized compound 12, characterized by the presence of a 3-oxabicyclo[4.1.0]heptane all-carbon quaternary morpholine surrogate, as a multitarget (PI3K/AKT/MTOR) inhibitor. 55 The X-ray structure of 12 revealed coplanarity between the pyrimidine ring and the 3-oxabicyclo[4.1.0]heptane moiety. The authors postulated that the oxygen atom in a 3oxabicyclo[4.1.0]heptane ring is oriented optimally to engage in a key hydrogen bonding interaction with the target enzymes.…”
Section: Development Of G-protein-coupled Bile Acidmentioning
confidence: 99%
“…Several morpholine-containing pharmacophores have been identified as responsible for the selective interaction with specific molecular targets, such as aryl-morpholines interacting with PI3K kinase family or morpholine–azaindoles with cannabinoid receptors . They are structurally similar to endogenous neurotransmitters (as in the case of aryl-morpholines) and it has been demonstrated that they play a key role in improving the crossing of the blood-brain barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Just to give some examples, doxapram (1976), 26 phendimetrazine (1979), 27 moclobemide (1992), 28 reboxetine (1997), 29 and aprepitant (2003) 30−32 are drugs with applications in several CNS diseases, mainly as anxiolytics and/or antidepressants. Several morpholine-containing pharmacophores have been identified as responsible for the selective interaction with specific molecular targets, such as aryl-morpholines interacting with PI3K kinase family 33 or morpholine−azaindoles with cannabinoid receptors. 34 They are structurally similar to endogenous neurotransmitters (as in the case of arylmorpholines) and it has been demonstrated that they play a key role in improving the crossing of the blood-brain barrier.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[67,68] Even tertiary cyclopropane-containing trifluoroborates are sufficiently reactive; an example can be provided by potassium 3-oxabicyclo [4.1.0]heptan-6-yltrifluoroborate (53), which was used in the cross-coupling with pyrimidine derivative 54 (Scheme 15 A). [69] This transformation was used by GSK scientists to introduce the 3-oxabicyclo[4.1.0]heptane motif as a morpholine isostere without a nitrogen atom and to develop novel inhibitors of the PI3 K-AKT-mTOR signaling pathway. A similar process involving azabicyclo[n.1.0]alkane-derived trifluoroborates 56 was used by Pfizer chemists in the synthesis of clinical candidates for the pain treatment.…”
Section: Suzuki-miyaura Cross-couplingmentioning
confidence: 99%